Synthesis, characterization, and antibacterial activity of 6-Chloro-8-methyl-2-oxo-2H-chromene-3-carboxylic acid ethyl ester. (2nd January 2016) - Latha Rani, N.; Prashanth, T.; Sridhar, M. A.; Gurupadaswamy, H. D.; Shaukath Ara, K.; Lokanath, N. K.
ABSTRACT: The title compound was synthesized by reacting 2-hydroxy-4-methoxy-benzaldehyde with diethyl malonate in the presence of piperidine catalyst and ethanol as solvent. The chemical structure of the title compound was elucidated by elemental analysis, 1 H-NMR, and IR. The crystal structure was determined by X-ray diffraction data. It crystallizes in monoclinic crystal system, P21 /c space group with unit cell parameters, a = 12.840(2) Å, b = 24.790(4) Å, c = 7.8544(13) Å, β = 98.035(5)°, V = 2475.5(7) Å 3, and Z = 8. The molecular and crystal structure of the title compound is stabilized by inter- and intramolecular interactions of the type C—H···O. The newly synthesized compound was screened for its antibacterial activity against two gram-positive and two gram-negative bacteria.